Management fundamentals concepts, applications, skill development - Lussier, Robert N. (SAGE Publications, Inc., 2021)
"Packed with experiential exercises, self-assessments, and group activities, the Ninth Edition of Management Fundamentals develops essential management skills students can use in their personal and professional lives. Bestselling author Robert N. Lussier uses the most current cases and examples to illustrate management concepts in today's ever-changing business world. This fully updated new edition provides in-depth coverage of key AACSB topics such as diversity, ethics, technology, and globalization. New to this Edition: 18 new cases on real-world organizations and people including NBA, H&M, Peleton, Netflix, FoxNews, Mary Barra and GM, Oprah New and expanded coverage of important topics like generational differences, sexual harassment, AI, cybersecurity, entrepreneurial mindset, managing change, and emotional intelligence Fully updated Trends and Issues in Management sections in each chapter New self-assessments on career readiness, gender views, religious knowledge, and preferred response styles Hundreds of new examples, statistics, and references so your students are exposed to the latest thinking in management"--Provided by publisher.